STRATEGI PUBLIKASI KEGIATAN MADRASAH MELALUI MEDIA SOSIAL TIKTOK DALAM PENINGKATAN BRAND IMAGE MTSN 5 KARAWANG - Agisna Nurhidayat; Muhamad Taufik Bintang Kejora; Yadi Fahmi Arifudin (STKIP Pesisir Selatan, 2026)
This study aims to analyze the strengths, weaknesses, opportunities, and threats of publicizing madrasah activities through TikTok, describe the publicizing strategies implemented, and identify the brand image that has been established at MTsN 5 Karawang. The study employs a descriptive qualitative approach with data collection techniques including observation, in-depth interviews with the madrasah principal, the vice principal for public relations, teachers, and students, as well as documentation. The results indicate that the madrasah’s primary strengths lie in its structured public relations team, authentic and diverse content, a professional account profile, and adequate production equipment support. Its weaknesses include time constraints for administrators due to dual roles and the suboptimal utilization of paid promotions. Publication strategies are implemented through three stages: content planning, activation and monitoring, and optimization. An evaluation of brand image based on eleven indicators showed that ten indicators were fully achieved and one was partially achieved, with a 95.5% achievement rate in the dimensions of creator image, user image, and product image. This study integrates social marketing theory, Schiffman and Kanuk’s brand image theory, and SWOT analysis.